The Korean Armistice - Bailey, Sydney D. author. aut Link
XIII, 312 p.
Keywords: Little is known by practitioners or academics about the dynamics of war termination. This book describes the negotiation and implementation of the armistice following the Korean war and the Korean phase of the Geneva conference (1954). It also analyzes some of the problems of coalition diplomacy. It thus foreshadows some of the problems that were encountered in conducting a UN-authorized war in the Gulf, and in the problems of negotiating a secure peace.